Transparent corrosion-resistant powder coating on glass surface of photovoltaic device and preparation method of transparent corrosion-resistant powder coating

By using thermoplastic solid acrylic resin, polyvinylidene fluoride resin, nano-silver-encapsulated zinc oxide core-shell structure particles and thiol-modified ZnSe/ZnS composite quantum dots on the surface of the glass plate of the photovoltaic device, the problem of corrosion-resistant powder coating of the surface coating of the photovoltaic device glass plate is solved, and the effects of high light transmittance, long-term stability and environmental protection are achieved.

CN119799080AActive Publication Date: 2025-04-11INST OF CORROSION SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510067411.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-11
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The surface coating of glass plates of existing photovoltaic devices is prone to corrosion and failure in harsh corrosion environments, making it difficult to meet the requirements of high light transmission, long-term stability and environmental protection.

Method used

A transparent corrosion-resistant powder coating including thermoplastic solid acrylic resin, polyvinylidene fluoride resin, nano-silver-encapsulated zinc oxide core-shell structure particles and thiol-modified ZnSe/ZnS composite quantum dots is used to improve the light transmittance and weather resistance of the coating through the synergistic effect of these raw materials.

Benefits of technology

It significantly improves the light transmittance and weather resistance of the glass surface coating of photovoltaic devices, extends the service life of the coating, and does not generate VOC emissions, making it more environmentally friendly due to the use of powder coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244676570000081
    Figure BDA0005244676570000081
Patent Text Reader

Abstract

The invention discloses a transparent corrosion-resistant powder coating on the glass surface of a photovoltaic device and a preparation method of the transparent corrosion-resistant powder coating, and belongs to the technical field of corrosion-resistant powder coatings. The powder coating is prepared from acrylic resin, polyvinylidene fluoride resin, a light-transmitting reinforcing filler A, a light-transmitting reinforcing filler B, a reinforcing agent, an antioxidant, a brightener, a flatting agent, benzoin and a defoaming agent, and is prepared by the following steps: firstly, adding the raw materials into an extruder, melting, mixing, extruding, crushing and screening to obtain the powder coating; after a glass substrate is preheated, powder coating is electrostatically sprayed on the surface of the substrate, and the transparent corrosion-resistant powder coating on the glass surface of the photovoltaic device is obtained after baking and cooling. The powder coating provided by the invention adopts the acrylic resin and the fluorocarbon resin as matrixes, and through the synergistic effect of the light-transmitting reinforcing materials, the powder coating is better in light transmission and weather resistance than common acrylic resin, does not generate VOC emission, and is more environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrosion-resistant powder coatings, and in particular relates to a transparent corrosion-resistant powder coating on the glass surface of a photovoltaic device and a preparation method thereof. Background Art

[0002] The photovoltaic industry is one of the new energy fields that has developed rapidly in recent years. The transparent glass on the surface of photovoltaic devices is an important part of the entire photovoltaic module. Its function is to maximize the absorption of solar energy while protecting the internal core components. However, photovoltaic glass panels are exposed to harsh natural environments all year round, such as high temperature and humidity, salt spray corrosion, high ultraviolet radiation, and wind and sand wear, which puts very high demands on the coating on the glass surface.

[0003] The main function of photovoltaic glass coating is to protect the glass substrate from environmental erosion, while ensuring the high light transmittance and long-term stability of the coating itself. Specifically, photovoltaic glass coatings must meet the following key requirements: First, high light transmittance. The coating must maximize the transmittance of sunlight (>90%) to improve the power generation efficiency of photovoltaic modules. Secondly, excellent weather resistance. The coating must be able to withstand long-term ultraviolet radiation, high temperature and humidity, and salt spray corrosion without performance degradation. In addition, the coating must also have good impact resistance and be able to avoid cracking or peeling during transportation, installation and service. At the same time, environmental protection is also an important indicator. The coating preparation process should minimize VOC emissions and avoid pollution to the environment. Finally, the coating should also have additional functionality, such as self-cleaning performance, which can effectively reduce dust adhesion, thereby maintaining long-term high-efficiency power generation performance.

[0004] Although existing coating technologies have been applied to photovoltaic glass panels, there are still many deficiencies in practical applications. For example, acrylic coatings have poor weather resistance and are prone to aging under ultraviolet and high humidity environments, resulting in a rapid decrease in light transmittance. Fillers in traditional coatings such as silica, titanium oxide, and glass powder are prone to light scattering due to poor dispersion and large particle size (>10nm), thereby reducing light transmittance. Therefore, in order to meet the needs of future development of the photovoltaic industry, a high-performance photovoltaic glass coating is urgently needed that can not only significantly improve light transmittance, but also maintain long-term stability in harsh environments. Summary of the invention

[0005] In view of the shortcomings of the prior art, and in order to solve the problem that the surface coating of the photovoltaic device glass plate is prone to corrosion and failure in harsh corrosive environments, the purpose of the present invention is to provide a transparent corrosion-resistant powder coating on the surface of photovoltaic device glass and a preparation method thereof.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention is to provide a transparent corrosion-resistant powder coating on the surface of photovoltaic device glass, which comprises the following raw materials in parts by weight: 16-30 parts of thermoplastic solid acrylic resin, 33-45 parts of polyvinylidene fluoride resin, 10-30 parts of light-transmitting enhancing filler A, 5-25 parts of light-transmitting enhancing filler B, 0.5-5 parts of reinforcing agent, 0.3-0.8 parts of antioxidant, 0.1-1 parts of brightener, 0.1-2 parts of leveling agent, 0.1-0.5 parts of benzoin, and 0.1-0.8 parts of defoaming agent.

[0008] In some embodiments, the thermoplastic solid acrylic resin is copolymerized by methyl methacrylate, ethyl acrylate, acrylic acid, and lauryl methacrylate; wherein the mass ratio of methyl methacrylate to ethyl acrylate is 32-42:8-18, and the glass transition temperature is 60-90°C.

[0009] It should be noted that the content of acrylic acid is 0.2-0.7% of the total mass of the raw materials; the content of lauryl methacrylate is 0.4-2% of the total mass of the raw materials. Methyl methacrylate is used to increase the glass transition temperature, hardness and weather resistance, ethyl acrylate is used to improve the flexibility, acrylic acid is used to improve adhesion, and lauryl methacrylate is used to improve water resistance and alcohol resistance.

[0010] Preferably, the molecular weight of the thermoplastic solid acrylic resin is 80,000-90,000; the molecular weight of the polyvinylidene fluoride resin is 300,000-450,000, and the melting point is 150-175°C.

[0011] It should be noted that thermoplastic solid acrylic resin has good physical and mechanical properties due to its large molecular weight, but its high melt viscosity affects its processability, pigment dispersion and leveling properties. The smaller the relative molecular weight of PVDF, the better its leveling and gloss, but the product has poor adhesion and acid resistance; when the relative molecular weight is large, the product has poor leveling, poor gloss, and poor acid and alkali resistance. Therefore, the molecular weight is limited in this technical solution, and the relative molecular weight should be moderate.

[0012] PVDF resin is a polymer with a tight and stable chemical structure formed by alternating -CH2- and -CF2- groups. The structure contains a large number of CF bonds, with a bond energy of up to 485KJ / mol, much higher than CH, CO, Si-O, Si-C, etc., and the CC bond main chain is surrounded by a series of negatively charged F atoms, forming a high-density three-dimensional shield to protect the stability of the CC bond, so it is difficult to be destroyed by light, heat, and chemical factors. Acrylic resin and polyvinylidene fluoride resin have different effects on impact resistance, weather resistance, and adhesion. Acrylic resin has good adhesion, but poor impact resistance and weather resistance. Fluorocarbon resin is added to improve weather resistance.

[0013] In some embodiments, the light-transmitting enhancing filler A is a nano-silver-encapsulated zinc oxide core-shell structure particle, which is prepared by the following preparation steps:

[0014] S1: Add zinc acetate dihydrate into methanol and stir to obtain solution 1;

[0015] S2: Add potassium hydroxide to methanol and stir to obtain solution 2;

[0016] S3: adding solution 2 dropwise to solution 1, cooling after the reaction is complete to obtain a solid product, and washing and annealing to obtain nano zinc oxide;

[0017] S4: The nano zinc oxide, sucrose, polyvinyl pyrrolidone and deionized water prepared in S3 are stirred and mixed to obtain solution three;

[0018] S5: adding sodium chloride solution to solution three, and then adding silver nitrate solution dropwise to obtain solution four;

[0019] S6: After the four reactions of the solution are completed, the solid product is obtained by centrifugation, and the nano-silver-encapsulated zinc oxide core-shell structure particles are obtained after washing and drying.

[0020] When Ag is combined with ZnO, the surface plasmon resonance effect of Ag can interact with the optical properties of ZnO to increase the light capture efficiency, thereby enhancing the light transmittance. In addition, Ag nanoparticles can act as electron traps, reduce the recombination of electron-hole pairs in ZnO, increase the lifetime of photogenerated charge carriers in the material, enhance the optoelectronic properties, and further improve the light transmittance.

[0021] Secondly, ZnO has wide-bandgap semiconductor properties and mainly responds to ultraviolet light, while the addition of the Ag shell can broaden the spectral response range of the entire composite material to the visible light region and enhance its light transmittance in a wider spectral range.

[0022] Finally, the core-shell structure can reduce the reflection loss of light on the surface of the material. The Ag shell can optimize the incident and transmission paths of light, allowing more light energy to enter the ZnO core and improve the overall light transmittance.

[0023] Preferably, the particle size of nano zinc oxide is 3-5 nm, and the thickness of the silver shell layer in the nano silver-encapsulated zinc oxide core-shell structure particles is 2-3 nm.

[0024] Preferably, in S3, solution one is maintained at 60-70°C and solution two is added dropwise, the reaction temperature is 60-70°C, the reaction time is 2-4h, the annealing temperature is 200-300°C, and the annealing time is 1-2h; in S6, solution four is placed in a hydrothermal reactor, and the hydrothermal reactor is placed in a heating device at 150-170°C for reaction for 12-13h.

[0025] It should be noted that too large a particle size of nano zinc oxide will cause light scattering, thereby reducing transmittance; poor dispersion will also lead to diffuse reflection of light, reducing transmittance, and the particle size of nano zinc oxide is optimal at 3nm-5nm. Reaction time is an important factor affecting the preparation of nano zinc oxide. A sufficiently long reaction time can ensure that the reaction is complete and zinc oxide crystals grow fully; but too long a reaction time will lead to excessive growth and agglomeration of grains, so it is necessary to control the S3 reaction time to 2-4h to obtain ideal nano zinc oxide particles.

[0026] In some embodiments, the light-transmitting enhancing filler B is thiol-modified ZnSe / ZnS composite quantum dots, and the particle size of the ZnSe / ZnS composite quantum dots is 2-8 nm.

[0027] It should be noted that compared with other composite quantum dots such as CdSe / ZnS, ZnSe / ZnS composite quantum dots have the following advantages:

[0028] ZnSe / ZnS composite quantum dots have a wide band gap, a high refractive index and a low absorption coefficient, a high absorption capacity for ultraviolet light, and a high transmittance for visible light, which helps to enhance the overall light transmittance of the coating while blocking harmful ultraviolet light. In addition, ZnSe has good chemical stability. When combined with the core-shell structure of ZnS, it exhibits higher stability in long-term illumination and environmental exposure, making it suitable for more demanding outdoor photovoltaic applications. In addition, the thiol-modified organic layer provides a protective barrier on the surface of the quantum dots to prevent oxidation and moisture intrusion, thereby improving the optical stability and long-term service life of the composite quantum dots; thiol molecules can also effectively passivate the defect states on the surface of ZnS / ZnSe quantum dots, reduce light absorption losses caused by surface and internal defects, and reduce light scattering, so that more light can pass through the material without being absorbed or scattered, thereby improving light transmittance. ZnSe / ZnS does not contain harmful heavy metal elements, complies with environmental regulations, and is an ideal material for green photovoltaic technology.

[0029] Thiol-modified ZnSe / ZnS composite quantum dots were prepared by the following steps:

[0030] 1. Preparation of ZnSe / ZnS composite quantum dots by hot injection method:

[0031] 15mmol of zinc stearate was added into a three-necked flask, and then 500ml of 1-octadecene was added, and then the mixture was slowly heated to 240℃, and the water vapor in the three-necked flask was evacuated with a vacuum pump; at 240℃, 15mmol of Se precursor (selenium powder-1-octadecene solution) was injected, and the mixture was slowly heated to 270℃ and kept for 20min to obtain ZnSe cores;

[0032] The temperature was lowered to 260°C, and 5 ml of sulfur precursor (i.e., 5 mol / L sulfur in octadecene solution) and 5 ml of Zn precursor (i.e., 0.25 mol / L zinc stearate in octadecene solution) were slowly injected. The temperature was lowered to 250°C and maintained for 30 min, and then cooled to room temperature. After centrifugation, the mixture was washed with methanol and acetone for 3 to 4 times to obtain ZnSe / ZnS composite quantum dots, which were stored away from light.

[0033] 2. ZnSe / ZnS composite quantum dot modification:

[0034] In a dark environment, the composite quantum dots were dispersed in a mixed solvent of toluene and cyclohexane in a mass ratio of 1:1000, argon was passed, stirred, and refluxed for 2 to 3 hours, and then KH590 (the mass ratio of KH590 to ZnSe / ZnS composite quantum dots was 1:0.3 to 0.5) was added dropwise, and stirred and refluxed for 24 hours to allow the silane group to combine with the surface of the quantum dots to form a stable Si-O bond; after centrifugation, the modified substance Y was obtained by washing with ethyl acetate and petroleum ether;

[0035] 1-hexadecyl mercaptan was dissolved in toluene at 65°C, the above-mentioned modifier Y was added (the mass ratio of the modifier Y to 1-hexadecyl mercaptan was 10-15:1), argon was passed, and the reaction was refluxed at 65°C for 24 hours to allow the long-chain alkyl mercaptan to combine with the thiol groups on the surface of the quantum dots to enhance the hydrophobicity; after centrifugation, the mixture was washed with ethyl acetate and petroleum ether to obtain thiol-modified ZnSe / ZnS composite quantum dots.

[0036] In some embodiments, the reinforcing agent is a single-layer graphene; the antioxidant is at least one of hindered phenols and phosphites; the brightener is a copolymer of butyl acrylate and methyl methacrylate; the leveling agent is an acrylate leveling agent; and the defoaming agent is a wax defoaming agent.

[0037] Among them, the absorption of visible light by single-layer graphene is extremely low, with a light absorption rate of only about 2.3%. This high light transmittance allows graphene to provide effective UV shielding without significantly affecting the transparency of the coating. Graphene can improve the mechanical properties of the coating, and its two-dimensional sheet structure can also delay the penetration of water and oxygen, and has a good shielding effect on ultraviolet rays. It can provide UV protection without significantly affecting the visible light transmittance, thereby extending the service life of the coating, especially in outdoor environments. The enhancer can also choose a few-layer boron nitride nanosheet h-BN.

[0038] Preferably, the brightener is 701 auxiliary agent, the leveling agent is GLP588 or TC486 leveling agent, and the defoamer is BYK961 defoamer.

[0039] The second aspect of the present invention is to provide a method for preparing a transparent corrosion-resistant powder coating on the surface of photovoltaic device glass, comprising the following steps:

[0040] S1: adding raw materials into the extruder, extruding after melting and mixing, and crushing and screening into powder coating;

[0041] S2: After the glass substrate is preheated, powder coating is electrostatically sprayed on the substrate surface, and after baking and cooling, a transparent corrosion-resistant powder coating on the surface of the photovoltaic device glass is obtained.

[0042] In some embodiments, in S1, the melting temperature is 170-190°C, and the particle size of the powder coating is 30-40 μm; in S2, the preheating temperature is 50-90°C, the preheating time is 10-30 min, the electrostatic voltage is 60-80 kV, the baking temperature is 230-260°C, and the baking time is 10-25 min.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] 1. The coating provided by the present invention is a powder coating, which does not produce VOC emissions compared to water-based or oily acrylic coatings and is more environmentally friendly.

[0045] 2. The transparent corrosion-resistant powder coating on the surface of the photovoltaic device glass provided by the present invention uses acrylic resin and fluorocarbon resin as a matrix, and through the synergistic effect with the light-transmitting enhancing filler, it has better light transmittance and weather resistance than general acrylic resin.

[0046] 3. The present invention introduces light-transmitting enhancement filler A—nanosilver-encapsulated zinc oxide core-shell structure particles (ZnO@Ag) and light-transmitting enhancement filler B—thiol-modified nano zinc sulfide / zinc selenide (ZnS / ZnSe) composite quantum dots. Light-transmitting enhancement filler A has excellent light transmittance in a wide spectrum, and the core-shell structure can reduce the reflection loss of light on the surface of the material; light-transmitting enhancement filler B has a high absorption capacity for ultraviolet light, a high transmittance for visible light and an ultra-small particle size (<10nm), and the thiol-modified organic layer forms a protective barrier on the surface of the quantum dots to prevent oxidation and moisture intrusion. The synergistic effect of the two light-transmitting enhancement fillers can significantly improve the light transmittance, UV resistance, optical stability and service life of the coating. DETAILED DESCRIPTION

[0047] The present invention is further described in detail below. The embodiments described are exemplary and intended to explain the present invention, but should not be construed as limiting the present invention.

[0048] Example 1

[0049] A transparent corrosion-resistant powder coating for the surface of photovoltaic device glass, comprising the following raw materials by weight: 23 parts of acrylic resin, 35 parts of polyvinylidene fluoride resin, 30 parts of light-transmitting enhancing filler A, 8 parts of light-transmitting enhancing filler B, 1 part of reinforcing agent, 0.5 parts of antioxidant, 1 part of brightener, 1 part of leveling agent, 0.4 parts of benzoin, and 0.1 parts of defoaming agent;

[0050] Among them, the acrylic resin is copolymerized by methyl methacrylate, ethyl acrylate, acrylic acid and lauryl methacrylate, and the ratio of methyl methacrylate to ethyl acrylate is 32:8; the content of acrylic acid is 0.5% of the total mass of the raw materials; the content of lauryl methacrylate is 1.2% of the total mass of the raw materials.

[0051] The above-mentioned light-transmitting enhancing filler A is a nano-silver-encapsulated zinc oxide core-shell structure particle, which is prepared by the following steps:

[0052] Preparation of zinc oxide core: zinc oxide nanoparticles were prepared by hydrothermal method. 0.01 mol zinc acetate dihydrate was weighed and added to 125 mL methanol. The mixture was stirred vigorously at 60 ° C for 1 h to fully dissolve the zinc acetate dihydrate to obtain solution 1. 0.03 mol potassium hydroxide was weighed and added to 65 mL methanol. The mixture was stirred and dissolved to obtain solution 2. While solution 1 was stirred at 60 ° C, solution 2 was added dropwise to solution 1. After the addition was completed, the reaction was continued at 60 ° C for 2 h. After the reaction was completed, the reactant was cooled and washed three times with methanol to remove impurities. After washing, it was dried for standby use to obtain nano zinc oxide.

[0053] Preparation of nanosilver-encapsulated zinc oxide nanoparticles: Weigh 0.2g of nanozinc oxide, 0.5g of sucrose, 4g of polyvinyl pyrrolidone, and deionized water into a beaker and stir to obtain a clear solution. Add 50mL of 0.04mol / L NaCl solution to the clear solution and stir for 0.5h. Then use a peristaltic pump to drop 20mL of 0.03mol / L silver nitrate solution into the mixed solution (dropping speed is 1mL / min), and the resulting milky white suspension is transferred to a hydrothermal reactor and reacted in an oven at 160°C for 12h. After centrifugation, the product was washed several times with deionized water and anhydrous ethanol, dried in vacuum at 80°C for 8h, and annealed at 200°C for 2h to obtain the final product-transparent enhanced filler A (ZnO@Ag), with a particle size of 5-8nm.

[0054] The above-mentioned light-transmitting enhancing filler B is a ZnSe / ZnS composite quantum dot modified with thiol, which is prepared by the following preparation method:

[0055] 1. Preparation of ZnSe / ZnS composite quantum dots by hot injection method:

[0056] 15mmol of zinc stearate was added into a three-necked flask, and then 500ml of 1-octadecene was added, and then the mixture was slowly heated to 240℃, and the water vapor in the three-necked flask was evacuated with a vacuum pump; at 240℃, 15mmol of Se precursor (selenium powder-1-octadecene solution) was injected, and the mixture was slowly heated to 270℃ and kept for 20min to obtain ZnSe cores;

[0057] The temperature was lowered to 260°C, and 5 ml of sulfur precursor (i.e., 5 mol / L sulfur in octadecene solution) and 5 ml of Zn precursor (i.e., 0.25 mol / L zinc stearate in octadecene solution) were slowly injected. The temperature was lowered to 250°C and maintained for 30 min, and then cooled to room temperature. After centrifugation, the mixture was washed with methanol and acetone for 4 times to obtain ZnSe / ZnS composite quantum dots, which were stored away from light.

[0058] 2. ZnSe / ZnS composite quantum dot modification:

[0059] The composite quantum dots were dispersed in a mixed solvent of toluene and cyclohexane in a mass ratio of 1:1000 in a dark environment, argon was passed, stirred, and refluxed for 3 hours, and then KH590 (the mass ratio of KH590 to ZnSe / ZnS composite quantum dots was 1:0.4) was added dropwise, and stirred and refluxed for 24 hours to allow the silane group to combine with the surface of the quantum dots to form a stable Si-O bond; after centrifugation, the mixture was washed with ethyl acetate and petroleum ether to obtain a modified substance Y;

[0060] 1-Hexadecyl mercaptan was dissolved in toluene at 65°C, and the above-mentioned modified substance Y (the mass ratio of ZnSe / ZnS composite quantum dots to 1-hexadecyl mercaptan was 13:1) was added, and argon was passed through. The reaction was refluxed at 65°C for 24 hours to allow the long-chain alkyl mercaptan to combine with the thiol groups on the surface of the quantum dots to enhance the hydrophobicity; after centrifugation, the mixture was washed with ethyl acetate and petroleum ether to obtain thiol-modified ZnSe / ZnS composite quantum dots.

[0061] The transparent corrosion-resistant powder coating on the surface of the photovoltaic device glass is obtained by the following preparation method, comprising the following steps:

[0062] S1: acrylic resin, polyvinylidene fluoride resin, light-transmitting enhancing filler A, light-transmitting enhancing filler B, monolayer graphene, antioxidant (BASF Irganox B225), brightener (Ningbo Weikai Chemical WK701), leveling agent (Troy TC486), benzoin, defoamer (BYK BYK961) were added into a twin-screw extruder according to weight proportions, melt-mixed at 180°C and extruded, and crushed and sieved to obtain a powder coating with a particle size of 35 μm;

[0063] S2: After the glass substrate is preheated in an oven at 70°C for 30 minutes, powder coating is electrostatically sprayed on the surface of the substrate. The electrostatic spraying voltage is 65 kV. The sprayed sample is placed in an oven at 250°C and baked for 20 minutes. It is taken out and naturally cooled to room temperature to obtain a transparent corrosion-resistant powder coating on the glass surface of the photovoltaic device.

[0064] Example 2

[0065] The raw materials and preparation method are the same as those in Example 1, except that: the light-transmitting enhancing filler A is 20 parts, the light-transmitting enhancing filler B is 16 parts, the enhancing agent is 3 parts; and the ratio of methyl methacrylate to ethyl acrylate is 42:18.

[0066] Example 3

[0067] The raw materials and preparation method are the same as those in Example 1, except that: the light-transmitting enhancing filler A is 10 parts, the light-transmitting enhancing filler B is 24 parts, the reinforcing agent is 5 parts; and the ratio of methyl methacrylate to ethyl acrylate is 37:13.

[0068] Example 4

[0069] The raw materials and preparation method are the same as those in Example 1, except that: 18 parts of acrylic resin, 42 parts of polyvinylidene fluoride resin, 10 parts of light-transmitting enhancing filler A, 24 parts of light-transmitting enhancing filler B, and 3 parts of enhancer.

[0070] Comparative Example 1

[0071] The raw materials and preparation method are the same as those in Example 4, except that: 42 parts of acrylic resin and 18 parts of polyvinylidene fluoride resin.

[0072] Comparative Example 2

[0073] The raw materials and preparation method are the same as those in Example 3, except that: no light-transmitting enhancing filler A, light-transmitting enhancing filler B, or reinforcing agent is added.

[0074] Comparative Example 3

[0075] The raw materials and preparation method are the same as those in Example 3, except that no light-transmitting enhancing filler B is added.

[0076] Comparative Example 4

[0077] The raw materials and preparation method are the same as those in Example 3, except that no light-transmitting enhancing filler A is added.

[0078] Performance Testing

[0079] In order to prove that the transparent corrosion-resistant powder coating on the surface of photovoltaic device glass provided by the present invention has excellent light transmittance and weather resistance, performance tests were conducted on Examples 1-4 and Comparative Examples 1-4. The aging resistance test of the coating was conducted according to method A cycle 1 in standard GB / T16422.3-2022, the impact resistance test of the coating was conducted according to standard SY / T 0315-2013, the light transmittance test of the coating was conducted according to standard GB / T2410-2008, and the wet adhesion of the coating was conducted according to standard GB / T 5237.4-2017. The performance test data are shown in Table 1.

[0080] Table 1 Performance comparison between Examples 1-4 and Comparative Examples 1-4

[0081]

[0082] As can be seen from Table 1, the initial light transmittance of the embodiments is higher than that of the comparative examples, indicating that the synergistic effect of the light-transmitting enhancing fillers A, B and the enhancer can greatly improve the light transmittance of the coating. In addition, the light transmittance of the coatings of comparative examples 3 and 4 is higher than that of comparative example 2 to varying degrees, indicating that both the light-transmitting enhancing fillers A and B play a role in improving the light transmittance of the coating;

[0083] The initial light transmittance of Example 4 is lower than that of Examples 1-3, but the degree of decrease in its light transmittance after 2500 hours of UV aging is significantly smaller, indicating that the increase in the fluorocarbon resin content will have a negative effect on the initial light transmittance of the coating, but it helps to improve the weather resistance of the coating, so that the coating can maintain a high light transmittance when serving outdoors for a long time, reducing the impact on power generation efficiency.

[0084] It can be seen from Example 4 and Comparative Example 1 that excessive acrylic resin and insufficient polyvinylidene fluoride resin cannot meet the performance requirements of the coating. The mixing ratio of the two has different effects on impact resistance, weather resistance and adhesion, and a suitable ratio is very important.

[0085] The method for preparing the transparent corrosion-resistant powder coating on the glass surface of a photovoltaic device provided by the present invention introduces light-transmitting reinforcing filler and polyvinylidene fluoride resin into the traditional acrylic coating, which not only ensures the light transmittance of the coating but also significantly improves the weather resistance of the coating, and has great application potential.

[0086] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A transparent corrosion-resistant powder coating on the surface of photovoltaic device glass, characterized in that: The invention comprises the following raw materials by weight: 16-30 parts of thermoplastic solid acrylic resin, 33-45 parts of polyvinylidene fluoride resin, 10-30 parts of light-transmitting reinforcing filler A, 5-25 parts of light-transmitting reinforcing filler B, 0.5-5 parts of reinforcing agent, 0.3-0.8 parts of antioxidant, 0.1-1 parts of brightener, 0.1-2 parts of leveling agent, 0.1-0.5 parts of benzoin and 0.1-0.8 parts of defoaming agent.

2. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 1, characterized in that: The thermoplastic solid acrylic resin is copolymerized by methyl methacrylate, ethyl acrylate, acrylic acid and lauryl methacrylate; wherein the mass ratio of methyl methacrylate to ethyl acrylate is 32-42:8-18, and the glass transition temperature is 60-90°C.

3. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 2, characterized in that: The molecular weight of the thermoplastic solid acrylic resin is 80,000-90,000; the molecular weight of the polyvinylidene fluoride resin is 300,000-450,000, and the melting point is 150-175°C.

4. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 1, characterized in that: The light-transmitting enhancing filler A is a nano-silver-encapsulated zinc oxide core-shell structure particle, which is prepared by the following preparation steps: S1: Add zinc acetate dihydrate into methanol and stir to obtain solution 1; S2: Add potassium hydroxide to methanol and stir to obtain solution 2; S3: adding solution 2 dropwise to solution 1, cooling after the reaction is completed to obtain a solid product, and washing and annealing to obtain nano zinc oxide; S4: The nano zinc oxide, sucrose, polyvinyl pyrrolidone and deionized water prepared in S3 are stirred and mixed to obtain solution three; S5: adding sodium chloride solution to solution three, and then adding silver nitrate solution dropwise to obtain solution four; S6: After the four reactions of the solution are completed, the solid product is obtained by centrifugation, and the nano-silver-encapsulated zinc oxide core-shell structure particles are obtained after washing and drying.

5. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 4, characterized in that: The particle size of the nano zinc oxide is 3-5 nm, and the thickness of the silver shell layer in the nano silver-encapsulated zinc oxide core-shell structure particles is 2-3 nm.

6. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 4, characterized in that: In the S3, solution one is kept at 60-70°C and solution two is added dropwise, the reaction temperature is 60-70°C, the reaction time is 2-4h, the annealing temperature is 200-300°C, and the annealing time is 1-2h; in the S6, solution four is placed in a hydrothermal reactor, and the hydrothermal reactor is placed in a heating device and reacted at 150-170°C for 12-13h.

7. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 1, characterized in that: The light-transmitting enhancement filler B is thiol-modified ZnSe / ZnS composite quantum dots, and the particle size of the ZnSe / ZnS composite quantum dots is 2-8 nm.

8. The transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to claim 1, characterized in that: The reinforcing agent is a single-layer graphene; the antioxidant is at least one of hindered phenols and phosphites; the brightener is a copolymer of butyl acrylate and methyl methacrylate; the leveling agent is an acrylate leveling agent; and the defoaming agent is a wax defoaming agent.

9. A method for preparing a transparent corrosion-resistant powder coating on the surface of photovoltaic device glass according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: adding raw materials into the extruder, extruding after melting and mixing, and crushing and screening into powder coating; S2: After the glass substrate is preheated, powder coating is electrostatically sprayed on the substrate surface, and after baking and cooling, a transparent corrosion-resistant powder coating on the surface of the photovoltaic device glass is obtained.

10. The preparation method according to claim 9, characterized in that: In S1, the melting temperature is 170-190°C, and the particle size of the powder coating is 30-40 μm; in S2, the preheating temperature is 50-90°C, the preheating time is 10-30 min, the electrostatic voltage is 60-80 kV, the baking temperature is 230-260°C, and the baking time is 10-25 min.

Citation Information

Patent Citations

  • Optical coating composition, fluorescent optical membrane and preparation method thereof

    CN103408984A

  • Photo-conversion quantum dot, solar light collector and solar light collection device

    CN106433646A

  • Solar cell coated with ZnSe / ZnS colloidal quantum dots and preparation method thereof

    CN107452822A

  • Light scattering material, antibacterial master batch, microspheres and preparation method and application thereof

    CN116239823A

  • Transparent powder coating for photovoltaic panel adhesive film and preparation method of transparent powder coating

    CN116814127A